Spillovers to Low-Income Countries : Importance of Systemic Emerging Markets - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2012)
This paper documents the expanding economic linkages between low-income countries (LICs) and a narrow group of "Emerging Market leaders" that have become major players in regional and global trade and financial flows. VAR models show that these linkages have increased the share of growth volatility that can be attributed to foreign shocks in LICs. Dynamic panel models further analyze the impact of LIC trade orientation and production structure on the sensitivity to foreign shocks. The empirical results demonstrate that the elasticity of growth to trading partners' growth is high for LICs in Asia, Latin America and the Caribbean, and Europe and Central Asia. However, for commodity-exporting LICs in Sub-Saharan Africa and the Middle East, terms of trade shocks and demand from the emerging market leaders are the main channels of transmission of foreign shocks.